2013
DOI: 10.1128/iai.00570-13
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T Cells Specific for a Malaria Cytoplasmic Antigen Form Clusters around Infected Hepatocytes and Are Protective at the Liver Stage of Infection

Abstract: cFollowing Anopheles mosquito-mediated introduction into a human host, Plasmodium parasites infect hepatocytes and undergo intensive replication. Accumulating evidence indicates that CD8 ؉ T cells induced by immunization with attenuated Plasmodium sporozoites can confer sterile immunity at the liver stage of infection; however, the mechanisms underlying this protection are not clearly understood. To address this, we generated recombinant Plasmodium berghei ANKA expressing a fusion protein of an ovalbumin epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 50 publications
6
58
0
Order By: Relevance
“…Nonetheless, a variety of lines of evidence support the notion that CD8 ϩ T cell killing occurs following cognate CD8 ϩ T cell-hepatocyte interactions. Recent independent in vivo imaging studies observed clustering of CD8 ϩ T cells around infected hepatocytes that led to the eventual killing of the parasites (10,11). Moreover, several in vitro and in vivo studies suggest that the infected cells themselves are able to present antigen directly to effector CD8 ϩ T cells (12)(13)(14)(15).…”
Section: Mmunization With Irradiated Sporozoites Induces a Cd8mentioning
confidence: 99%
“…Nonetheless, a variety of lines of evidence support the notion that CD8 ϩ T cell killing occurs following cognate CD8 ϩ T cell-hepatocyte interactions. Recent independent in vivo imaging studies observed clustering of CD8 ϩ T cells around infected hepatocytes that led to the eventual killing of the parasites (10,11). Moreover, several in vitro and in vivo studies suggest that the infected cells themselves are able to present antigen directly to effector CD8 ϩ T cells (12)(13)(14)(15).…”
Section: Mmunization With Irradiated Sporozoites Induces a Cd8mentioning
confidence: 99%
“…We used the P.berghei ANKA clone expressing GFP under the control of the hsp70 promoter (34), the P.berghei ANKA clone 676cl1 (Pb GFP-LUC sch ) expressing a GFP-luciferase fusion gene via the EEF1a promoter (35), the P. berghei ANKA clone deficient for SPECT2 (Sporozoite micronemal protein essential for cell traversal 2) and expressing GFP under the control of the hsp70 promoter (SPECT2F) (36), and the P.berghei ANKA clone PbA-hsOVA expressing class I and class II OVA epitopes (37).…”
Section: Parasitesmentioning
confidence: 99%
“…In the event that Plasmodium infected hepatocytes are still intact, processing may involve a direct cytosolic pathway where Ags that cross the PV and enter the cytosol would be degraded by proteasomes and then be transported by TAP to the ER for loading onto the nascent MHC I molecules. Studies with bone marrow chimeras showed that hepatocytes infected with P. berghei sporozoites expressing recombinant cytoplasmic fusion protein OVA-Hsp70 needed the classical TAP-dependent MHC class I pathway to process and present the OVA epitope [25]. Conversely, it has been reported that normal, healthy hepatocytes have very low levels of cathepsin S [59], an essential enzyme for TAP-independent processing [10].…”
Section: Discussionmentioning
confidence: 99%
“…At present, however, the identity of LS Ags that induce protracted protection in RAS-immunized mice remains largely unknown. More importantly, apart from the processing and presentation of the circumsporozoite protein (CSP) [24], the major sporozoite surface Ag and recombinant cytoplasmic fusion protein OVA-Hsp70 [25], pathways of processing and presentation of EE Ags for the induction of CD8 + T cells have not been investigated in the malaria system. Like infectious sporozoites, RAS enter the liver and invade hepatocytes where they undergo arrested development into LS parasites that express LS-specific Ags, but do not infect red blood cells (RBC) and hence do not cause clinical malaria.…”
Section: Introductionmentioning
confidence: 99%